Synthesis, Identification, and Study of the Antimicrobial and Antioxidant Activities of Some New 2,5-Disubstituted-1,3,4-Oxadiazole Derivatives - Ali, Rana Abid; Al-Tamimi, Entesar O.; Abdul Wadood, Shatha (Iraqi Journal of Science, 2024)
This study includes the synthesis of 2,5-disubstituted-1,3,4-oxadiazole 3-12 on creatinine derivatives that have antioxidant and microbial properties. The reaction of creatinine with hydrazine hydrate in absolute ethanol was successfully achieved to afford hydrazide derivatives 1,2. The desired 2,5-disubstituted-1,3,4-oxadiazoles 3-12 were obtained by the reaction of hydrazide derivatives with different aliphatic and aromatic acid derivatives in the presence of POCl3. FT-IR and 1H NMR spectroscopy were used to determine the structures of some compounds. The antioxidant activity of compounds 8, 9, 11, and 12, and the antimicrobial activity of compounds 1, 5, 11, and 12 were tested in vitro and showed good results.